The Role of Teacher Pedagogical Competence in Achieving Student Learning Achievement - Kerint M Simanjuntak; Briko A Siagian; Helena Turnip (edujavare, 2024)
Pedagogical competence is basically the teacher's knowledge and ability to educate and carry out learning. The purpose of writing this scientific article is to determine and describe the role of teachers' pedagogical competence in achieving student learning achievement, which includes aspects of student understanding and implementation of learning. By using the literature study method which is carried out by analyzing several journals that are relevant or suitable to the selected title, analysis can be carried out by reading, noting and processing the materials used as references and then drawing conclusions. Based on literature analysis, it was found that several things need to be emphasized in the process of planning and implementing learning, namely, readiness of teaching materials, appropriate learning methods, comfort during learning, and evaluation of learning outcomes and student development. To improve teacher pedagogical competence, schools must be able to provide mentoring and support to teachers to improve teacher pedagogical competence and in an effort to achieve learning achievement